Evidence of active tectonic movements in Krusne Hory Mts. (NW Bohemia) - Kostak,B. (Journal of the Czech Geological Society, 1998)
Two decades of deformation monitoring in the forefront of the CSA Mine at the toe of Krusne Hory Mts. (NW Bohemia) accumulated a large amount of data. Different monitoring methods were used primarily to assess mining effects upon the stability of adjacent mountainous fault slopes, and to secure safety in the mining operations. Two survey galleries driven into steep hills of Jezerka and Jezeri, opened an insight deep into the massif of crystalline rock, and into its behavior during a relatively long period of deformation. Evidence about horizontal creep, and of several episodic events of about half-a-year duration has been obtained. Some of them were due to mining, other of natural origin only. These have had apparently no connection with seismicity. In the period after the year 1991 there are clear indications of episodic movements that can be interpreted only as of natural tectonic origin. The movements include slope uplifts, as well as strain changes in the marginal zone of the mountains.
Keywords: Krusne Hory Mts.; Bohemia; active tectonic movements; crystalline rock deformation; monitoring of deformations